The Colima River and its use: El Chanal, a site in the Colima Valley - Alcántara Salinas, Andrés Saúl (2025)
Introduction: The development of Chanal, a culture in the Colima Valley that transcended not only this area, but its influence spanned from the coast of Manzanillo to Ciudad Guzmán. It is a culture with Mesoamerican influences, but that has a particular development, both in its settlement pattern and in the construction of architectural elements, taking advantage of the particularities of the environment, where the Colima River played a prominent role in achieving it. Objectives: Contribute to the research and dissemination of the work carried out at the INAH Colima Center, taking into account the institutional objectives, where the protection, conservation, research and dissemination of the archaeological heritage of our country based on the results of the Archaeological Project El Chanal. Method: The starting point is a case study of one of the postclassic sites of Western Mesoamerica, where the data addressed are part of the investigations of nine seasons of archaeological work. Results: Obtaining information about a culture, whose existence was unknown and which has allowed us to see the great knowledge they had of their environment and the way in which it was used, becoming one of the most important cultures in the Mesoamerican West. Conclusions: Publicizing the heritage of a nation in international forums always brings benefits to all parties, since feedback of knowledge is generated among the participants, which helps to improve research processes and thus better results. future.